2014
DOI: 10.1002/ijc.28961
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy to prevent chemotherapy and radiotherapy-induced alopecia using topically applied vasoconstrictor

Abstract: In a new strategy, we sought to determine whether topically applied vasoconstrictor, with its accompanying transient skin hypoxia and exclusion of systemic drug, would prevent or suppress radiotherapy or chemotherapy-induced alopecia. Topical vasoconstrictor was applied to 1-cm2 skin patches on the backs of 10-day-old rats and minutes later they received either 7.1 gray (Gy) whole-body radiation or systemic N-nitroso-N-methylurea (MNU) or Cytoxan. The degree of alopecia was scored 10 days later by visual asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Complete hair regrowth generally occurs within 2–4 months after irradiation [1014]. In addition, no treatment or preventive measures appear to be generally effective [19, 20]. To prevent this unwanted effect, awareness and limitation of radiation exposure to the patient are the most important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete hair regrowth generally occurs within 2–4 months after irradiation [1014]. In addition, no treatment or preventive measures appear to be generally effective [19, 20]. To prevent this unwanted effect, awareness and limitation of radiation exposure to the patient are the most important.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent this unwanted effect, awareness and limitation of radiation exposure to the patient are the most important. Although topical application of epinephrine or norepinephrine before radiation was found to confer up to 95% coat retention in a rat model, further studies in human are required to indicate its efficacy [19]. Online monitoring of the patient's radiation exposure is also necessary because fluoroscopy time does not account for either fluoroscopic dose rates or the use of fluorographic acquisition modes during a procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that topical application of the α-adrenergic vasoconstrictors epinephrine or NE to the skin of neonatal rats before a considerable radiation or chemotherapeutic insult prevented up to 100% of the alopecia observed in CTR animals [Soref and Fahl, 2015]. Chemotherapy-induced alopecia may be attributed to peripheral neurotoxic effects Dietrich et al, 2015], thus explaining why application of epinephrine or NE suppressed alopecia.…”
Section: Ne Promotes the Growth Of Hfmentioning
confidence: 99%
“…A strategy involving topical vasoconstrictor application for preventing radiotherapy and chemotherapy toxicities to skin and its organelles has emerged and has been proven effective in a preclinical study demonstrating suppression of radiation-or chemotherapy-induced alopecia (7) as well as in both preclinical and clinical studies showing up to 100% prevention of radiation dermatitis (8,9). A recent preclinical study has also shown efficacy of topical vasoconstrictor in suppression of oral mucositis in two separate animal models (10).…”
Section: Introductionmentioning
confidence: 99%